Physical Properties and Mineral Content of Sidoarjo Mud Volcano. (2015) - Handoko, Luky; Rifa'i, Ahmad; Yasufuku, Noriyuki; Ishikura, Ryohei
Abstract: Laboratory tests were conducted to assess the physical properties and mineral content of Sidoarjo mud volcano (or known as Lusi). These information are used to estimate the compression index which is considered to be important to support the reclamation program of the impoundment area. Physical properties of Lusi such as particle size distribution, Atterberg limits and specific gravity were determined in laboratory. Mineral content was observed through XRD test. Based on the Atterberg limit, the compression index was determined. The mineral content observed from the test are Chlorite and Illite. The results show that Lusi material consist of mostly fine-grained soil about 84.47% which dominated by clay size particle about 54.47% of total dry weight. Based on USCS it is classified as high plasticity silt (MH). New correlation has been proposed to estimate compression index from liquid limit and plasticity index using available data in literature. This new approach uses A-line in plasticity chart as boundary to database for developing the equations. Based on this separation of databases, more precise equations are obtained indicated by higher R value. Compression index of Lusi mud volcano is 0.367 from liquid limit-based calculation and is 0.454 from plasticity index-based calculation.